Implementasi Geocell Di Atas Tanah Dasar Pada Suatu Rencana Kawasan Wisata - Nova Sanchez Sitio; Andrias Suhendra Nugraha (Institut Teknologi Garut, 2026)
Road construction in tourism areas is often constrained by subgrade soil with low bearing capacity, which may cause deformation and reduce pavement performance. This study evaluates the application of HP15040C-type geocell in the base course layer over subgrade soil in a tourism area in West Bandung Regency using field CBR parameters. The research method used a quantitative case study approach through field observation, geocell installation, and field CBR testing in accordance with SNI 1738:2011 on three test areas covering approximately +-3,700 m2. The initial subgrade condition had a laboratory CBR value of 1.70 percent, indicating low bearing capacity. The 10th percentile analysis results showed characteristic CBR values of 58.84 percent in Area 1, 56.67 percent in Area 2, and 66.11 percent in Area 3. In addition, 90 percent of the CBR data from uniform segments showed minimum values of 60.44 percent in Area 1, 63.08 percent in Area 2, and 66.11 percent in Area 3. The findings indicate that geocell is capable of improving base course performance, with Area 3 meeting the CBR >= 60 percent criterion, while Area 1 and Area 2 approached the required value due to variations in field conditions. This study can serve as an initial reference for the application of geocell on tourism area roads with low-bearing-capacity subgrade soil.